Penjadwalan Perkuliahan dengan Metode Metaheuristic Ant Colony Optimization Studi Kasus Politeknik Negeri Bali - Komang Ayu Triana Indah; Putu Gede Sukarata (Unit Publikasi Ilmiah, P3M Politeknik Negeri Bali, 2019)
Lecture scheduling problems are a very complex problem, where the core of the scheduling is how to schedule several components consisting of students, lecturers, space, time, and subject matter with due regard to certain constraints and constraints. The goal to be achieved is to apply the Ant Colony Optimization (ACO) Metaheuristic method to optimize the lecture scheduling system. Every step taken by ACO uses an algorithm adapted from ant behavior to solve combinatorial problems. This system is created using Microsoft Visual Basic programming by entering several parameters, namely Lecturer, Course, Room, and several variables from each parameter which are then processed to produce lecture scheduling. The results obtained from the ACO implementation to solve college scheduling problems are seen from the number of constrained constraints and the length of time required from each iteration in each method to get a class schedule so that they get a schedule with a 82 percent truth level which is a comparison of constraint violations to the total number of timeslot used for scheduling.